2012
DOI: 10.1007/s00405-012-2102-8
|View full text |Cite
|
Sign up to set email alerts
|

Nasal obstruction following septorhinoplasty: how well does acoustic rhinometry work?

Abstract: Septorhinoplasty aims to improve not only the esthetic appearance but also breathing function of the nose. Although the esthetic improvement can be judged by the patient and the surgeon easily, evaluation of nasal breathing is more complicated. Besides the subjective symptom scores given by the patient, some objective methods have been developed. One of the most widely used of these objective methods is acoustic rhinometry, which gives valuable information about the cross-sectional areas and volumes of the nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…Grymer et al utilized acoustic rhinometry to demonstrate decreased nasal volume after rhinoplasty and osteotomies, providing a rationale for concurrent ITR to restore losses in nasal volume . However, volumetric measurements have not been demonstrated to correlate with symptoms of nasal obstruction, although the subsequent development of the NOSE instrument has allowed researchers to correlate patient‐reported symptoms of nasal obstruction with objective measurements. In this study, both SRP and SRPt cohorts improved, demonstrating that ITR is not required in all patients to achieve a significant clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grymer et al utilized acoustic rhinometry to demonstrate decreased nasal volume after rhinoplasty and osteotomies, providing a rationale for concurrent ITR to restore losses in nasal volume . However, volumetric measurements have not been demonstrated to correlate with symptoms of nasal obstruction, although the subsequent development of the NOSE instrument has allowed researchers to correlate patient‐reported symptoms of nasal obstruction with objective measurements. In this study, both SRP and SRPt cohorts improved, demonstrating that ITR is not required in all patients to achieve a significant clinical improvement.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies suggest longer efficacy for medial flap turbinoplasty beginning between 12 and 24 months, with lower reported revision rates (12%) compared to electrocautery (54%) or powered submucosal resection (i.e., microdebrider; 40%) during 60‐month follow‐up (n = 100) . These studies are limited by the lack of standardized outcomes, with measures based on rhinomanometry and acoustic rhinometry of unclear clinical significance given the lack of established correlation with PROMs . Ongoing analyses in large studies will be required to continue probing longitudinal, clinically significant differences between ITR techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Ozkul et al 18 showed an improvement in NIPF after septoplasty in 50 patients and concluded that this was a good method of evaluating nasal patency as his results were comparable to a control group of 219 patients. Edizer et al, 19 on the other hand, did not find a correlation between the improvement in nasal volume and symptomology following septorhinoplasty. Marais et al and Eren et al showed increases in NIPF values after septoplasty.…”
Section: Comparisons With Other Studiesmentioning
confidence: 92%
“…Edizer et al evaluated 26 patients undergoing septorhinoplasty for objective improvement in nasal airway using acoustic rhinometry and subjective improvements using a 10-point visual analog scale [ 8 ]. Although the patients all underwent septorhinoplasty, not all had preoperative complaints of nasal obstruction.…”
Section: Discussionmentioning
confidence: 99%